Peran Penggunaan Media Sosial Instagram dan Kepercayaan Pelanggan pada Loyalitas Pelanggan B2b UMKM - Verrent Senjaliani; Henky Lisan Suwarno (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In today's era filled with digital technology, business-to-business (B2B) sales forces are driven to strengthen relationships with customers through social media platforms. This aims to build a high level of trust. This research aims to test and analyze the factors influencing customer loyalty in the B2B context of Micro, Small, and Medium Enterprises (MSMEs), which include the use of social media, especially Instagram, and the level of trust in customer loyalty. This study uses a causal explanatory approach. The sample consists of MSMEs that have relationships with suppliers and actively use Instagram as part of their business activities. Data collection methods involve surveys with questionnaires distributed to 171 respondents. Data collection techniques use purposive sampling method and are then analyzed using PLS-SEM. This research concludes that social media usage significantly affects customer trust, customer trust significantly affects customer loyalty, and Instagram usage significantly affects customer loyalty mediated by customer trust.